Five hundred self-portraits - Bell, Julian, 1952-; Phaidon Press (London : Phaidon, 2000)
This text presents, without commentary, 500 of the world's greatest self-portraits, arranged in a chronological sequence from ancient Egypt to the late 20th century. Included are works by painters and sculptors such as Durer, Rembrandt and Picasso.
Includes index.
Keywords: Self-portraits.